Understanding novice teachers' perceived challenges and needs as a prerequisite for English curriculum innovation. Issue 1 (2nd January 2020) - Jiang, Anne Li; Zhang, Lawrence Jun; May, Stephen; Qin, Limin Tony
ABSTRACT: Teaching English for specific purposes (ESP) is widely acknowledged as highly demanding for teachers. Currently in China itself, shifting the curriculum focus from General English to ESP in the provision of English language education is regarded as a curriculum innovation. And yet, scarcely any research has probed into the challenges facing novice ESP teachers, along with their related needs for institutional support, in order to implement such a curriculum innovation successfully. To address this lacuna, we developed the ESP Teachers' Challenges and Needs Questionnaire (ESP-TCNQ), which was completed by 208 Chinese novice ESP teachers. Statistical methods were used for identifying typical patterns. Our exploratory factor analyses produced four dimensions representing major challenges and needs respectively for ESP teachers. To further verify the nature of institutional support needed, we conducted semi-structured interviews with six selected participants. Results show primarily two types of institutional support required for effective ESP provision, namely, policy and financial. They are closely related to the themes of self-directed learning, interdisciplinary liaison and collaboration, research activities, and pedagogical learning opportunities. Implications for curriculum innovation in terms of reconceptualising teacher knowledge and skills, and revisiting university organisational culture, are also discussed.